ENGLISH LANGUAGE PROFICIENCY ACHIEVEMENT IN 180 HOURS AMONG 2006 BATCH AT UNIVERSITAS ADVENT INDONESIA - Katemba, Caroline V.; Simarmata, Linda; Hendriks, Anne Lou (Journal of Language Pedagogy, 2011)
Nowadays, English is an official language around the world.  Many people have problem for communicating because they do not know English.  To exceed the problem, it is important to study English more and take Test of English as a Foreign Language (TOEFL) because it can help them to develop their English ability.   The objective of this study is to contribute to this discussion by examining: If there is any significant difference in achievement of English language proficiency of the participants after taking English for 180 hours during six semesters.   The participants were 63 young adult, they were 2006 batch enrolled in Universitas Advent Indonesia.  The participants of this study have taken English Entrance Exam (E3in) in the first semester and English Exit Exam (E3exit) in the 6th semester.   This research obtained the data as follows: X (E3in) as pre-test=63, Y (E3exit) as post-test=63.  The means of pre-test was 353.65 with mean standard deviation was 24.488 and with mean standard error was 3.085.  And after the treatments, the mean of post-test was 443.83 with mean standard deviation was 32.001 and with mean standard error was 4.032. The mean gain score between the two tests was 90.17.  This result was supported by t-counted result was 2.636 and t-table result was 1.671.  It means that t-counted > t-table. Thus, Ha is accepted, that there is a significant difference of achievement in English language proficiency after taking English for 180 hours during six semesters.